Hidden Carers? a Scoping Review of the Needs Of Carers of People with HIV in the Contemporary Treatment Era. (1st December 2018) - Hamilton, Myra; Botfield, Jessica; Persson, Asha; Newman, Christy; Bryant, Joanne; Valentine, Kylie; Wallace, Jack
Abstract : The role of carers in supporting people with HIV is largely hidden in Western countries in the contemporary era of antiretroviral treatments. Little is known about their needs. A scoping review was undertaken to describe the research available on the needs of this group and identify gaps in existing knowledge. Findings reveal that carers of people with HIV have similar needs to other carers but are currently mostly invisible to support services. The article suggests that the discourse of independence underpinning the new HIV treatment era may be difficult for carers to 'disrupt' by naming what they do as 'care'.